Significance of the conditions in criminal activity (on the example of corruption crimes) - Shabanov, Vyacheslav B.; Krasikau, Vladimir S. (Journal of the Belarusian State University. Law, 2020)
In the article from the point of view of forensic science, criminal procedure and operational-search activity, the theoretical and practical aspects of the prevention of corruption-related criminal activity are investigated in terms of identifying and neutralizing its conditions. The conclusion is substantiated that the conditions of a corruption crime are covered by the concept of criminal activity, which is subject to proof in the framework of the criminal process. A distinction is made between the subjects of the study of criminalistics and criminology in terms of the prevention of crime.
Keywords: criminalistics; operational-search activity; investigation of corruption crimes; crime prevention; causes and conditions of corruption crimes; legal liability; criminal corruption activity